Otolaryngologist surgical preferences for orbital decompression in thyroid eye disease: A North American survey - Ryan C. Higgins; Ciaran F. Lane; Neerav Goyal (Laryngoscope Investigative Otolaryngology)
Abstract Background Orbital decompression is recommended for TED especially in the treatment of severe, refractory cases yet there are no clear guidelines regarding the optimal surgical approach. Previously conducted surveys assessed variations in the management of TED but only amongst ophthalmologists. Our study attempts to better characterize surgical and perioperative preferences amongst otolaryngologists in the management of TED. Methods A survey was administered to the American Rhinologic Society and Canadian Society of Otolaryngology – Head and Neck Surgery via REDCap with 52 total respondents. Respondent demographic information and pre‐operative management, procedural specifics, and post‐operative management preferences were collected. Results The majority of respondents practiced in a metropolitan (82.7%), academic setting (73.1%) and received subspecialty training in Rhinology & Skull Base Surgery (88.9%). Most elected for corticosteroids (63.5%) and medical management (69.2%) prior to orbital decompression but did not use any classification system (86.5%). Orbital decompression was most often done with ophthalmology collaboration (71.2%). Removal of two bony walls (55.8%) via medial wall (97.9%) and orbital floor (72.3%) removal was most preferred. Removal of one orbital fat aspect (60.6%) via the medial fat pad was most preferred. Combined bone and fat removal (59.6%) completed via an endoscopic approach (71.2% and 97.0%, respectively) was most common. Post‐operatively, most patients were not admitted (88.4%) with saline nasal rinses (92.3%) utilized by most respondents. Conclusions This survey completed by otolaryngologists highlights several key distinctions in the preferred surgical approach during orbital decompression and the perioperative management of TED when compared to ophthalmologists and current recommendations. Level of evidence Level 4.